The Effect of Using Desktop Prezi Learning Media towards Student Learning Outcomes on Intermolecular Forces - Raudhaton Nur; Latifah Hanum; Zulfadli Zulfadli (FKIP USK, 2022)
AbstractThe research, entitled “The Effect of Using Prezi Desktop Learning Media on Students Learning Outcomes on Intermolecular Force Material”, was conducted in class X IPA MAS Ulumul Qur’an Banda Aceh City. The purpose of this study was to analyze the affect of using Prezi learning media on learning outcomes, describe student learning activities and analyze student responses to Prezi learning media applied to intermolecular forces material. This study used a quantitative approach with a quasi-experimental type of research. The research instrument used in the form of test questions, student activity observation sheets and student response questionnaire sheets. Data analysis using t-test obtained t-count results were greater than t-table using a significant level of 0,05, namely 2,692 1,671, which means accepting Ha. The results of student activity observations obtained from student activity sheets in the experimental class of yhe first meeting were 81,77% in the active category and 96,59 in the very active category at the second meeting. Students responses to the use of Prezi media on is said to very good, with a percentage of 89,9%. Based on the data obtained, it can be concluded that there is an effect of using Prezi learning media on student learning outcomes on intermolecular forces material and can increase student learning activities and obtain a very good response from students on the use of desktop Prezi as a learning medium Keywords: Prezi Desktop, Intermolecular Forces, Learning Media, Learning Outcomes